La vía de la responsabilidad civil por daño causado al can: a propósito de los supuestos de maltrato, crueldad o muerte del can. - Franciskovic Ingunza, Beatriz (2025)
The article aims to raise awareness of the importance of civil liability for damages caused to dogs, that is, in situations where a dog is the victim of harm, whether due to acts of abuse, cruelty, or the death of a dog, arising from a contractual or extracontractual relationship. This is due to the relationships of affection and attachment toward dogs, as they are considered an integral part of many families. The methodology used is qualitative, descriptive, and explanatory. Documentary analysis of specialized literature, police reports, analysis of court rulings, and national regulations was used. The results demonstrate that, independent of administrative and criminal proceedings, civil litigation can be used to seek compensation, especially when alleging moral damages due to the affection and feelings felt toward the dog.